Comment on Padraic X. Scanlan, Freedom’s Debtors: British Antislavery in Sierra Leone in the Age of Revolution - Rogers, Nicholas (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2019)
Padraic Scanlan’s Freedom’s Debtors makes an important intervention in the debate on the abolition of slavery by looking at what actually happened in Sierra Leone as it moved from company project to crown colony. Scanlan shows that anti-slavery advocates were not in practice equity advocates: slaves had to earn their freedom. In so doing he forces us to reconsider the manifold forms of bonded labour that characterised the Atlantic world and the imperatives of a globalizing market that demanded the continuing production of tropical staples by captive workforces, before and after slavery. Scanlan arguably blends abolition and emancipation in the opening phase of the British campaign to end the slave trade, but he shows, despite the humanitarian motives of some activists, that the full emancipation for slaves was conditional on their integration into global political economies.